The accessory fallopian tube, a rare Mullerian duct anomaly: two case report - Ibrahim Kale (Journal of the Pakistan Medical Association, 2020)
Abstract We describe two cases of accessory fallopian tubes which did not compromise fertilisation and were asymptomatic; the condition is rather rare. Both the cases were discovered during Caesarean sections; the first case featured accessory fallopian tubes attached to both the main tubes, while in the second case, two accessory tubes were attached to the right main tube. The fallopian tube is where fertilisation takes place; the zygote then proceeds to the uterine cavity. An accessory fallopian tube is a rare congenital anomaly; the tube is usually attached to the ampullary region of a principal tube. Accessory tubes are usually asymptomatic, rarely causing infertility, pyosalpingitis, tortion, and ectopic pregnancies. Key Words: Accessory fallopian tube, tubal duplication, fallopian tube, Mullerian duct anomaly. Continuous...